Automated soil penetrometer-shearometer for mapping the spatial variability of soil penetration resistance and shear stress. - Yahya, Azmi; Ng, Eng Boon (2008)

(untitled)
An automated soil penetrometer-shearometer unit (3) equipped with data acquisition and differential global positioning system (DGPS) is capable of real-time maping spatial variability of soil penetration resistance and shear stress associated with landscape position is disclosed. The unit consists of following four main sub-assemblies; a main frame (4) to support the moving carriage sub-assemblies, two moving carriage sub-assemblies (14,17) to support penetrometer (1) and sherometer (2), a gear driving mechanisms to support traverse movements of the moving carriages, and a three-point hitch attacment to support the main frame and provide attachment to the tractor. Motion controls for the penetrometer-shearometer unit (3) are performed by a Programmable Logic Controller (PLC) unit and other external electronics and sensing devices.